Agile processes in software engineering and extreme programming : 20th International Conference, XP 2019, Montréal, QC, Canada, May 21-25, 2019, Proceedings /: 20th International Conference, XP 2019, Montréal, QC, Canada, May 21-25, 2019, Proceedings. (2019) - Unknown
No abstract available